Amaren Beroa : A Ua Crag. - Museo San Telmo, San Sebastian; A Ua Crag; Peciña, José Ramón; Sáenz de Gorbea, Xabier (San Sebastian : Museo San Telmo, 1990)
A Ua Crag ; Lamata, Rafael ; Valle, Julián ; Criado, Rufo ; Max, Jesús ; Martínez, Alejandro ; Red District
Amaren Beroa, by A Ua Crag, Museo de San Telmo, San Sebastian
kunstcatalogus
Keywords: Catalonië